Sakralitas Sendekolo: Fenomena Spiritual Masyarakat Klaten Jawa Tengah - Hidayat, Rahmat; Widya Pangesti, Hestyana (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
People's belief in myths is often considered bad to violate. Klaten society is a society that believes in the sendekolo phenomenon, which is full of mystical things. Interestingly, people recognize the sendekolo phenomenon with different understandings. The purpose of this research is to examine how Klaten people understand the sendekolo phenomenon and how the community prevents this bad thing. The researcher used a qualitative approach with data collection techniques through interviews with seven informants who were recorded. The collected data is analyzed by reading it repeatedly, classifying it, and drawing conclusions. The theory used is Edward Evans Pritchard's anthropological theory. The results showed that Klaten people understand sendekolo as a sacred time that is full of taboos that apply to all ages. They also believe that certain objects are able to repel the spirits that roam during sendekolo.